Design and analysis of a lean interface for Sanskrit corpus annotation - Goyal, Pawan; Huet, Gerard (Journal of Language Modelling, 2016)
We describe an innovative computer interface designed to assist annotators in the efficient selection of segmentation solutions for proper tagging of Sanskrit corpora. The proposed solution uses a compact representation of the shared forest of all segmentations. The main idea is to represent the union of all segmentations, abstracting from the sandhi rules used, and aligning with the input sentence. We show that this representation provides an exponential saving, in both space and time. The segmentation methodology is lexicon-directed. When the lexicon does not have full coverage of the corpus vocabulary, some chunks of the input may fail to be recognized. We designed a lexicon-acquisition facility, which remedies this incompleteness and makes the interface more robust. This interface has been implemented, and is currently being applied to the annotation of the Sanskrit Library corpus. Evaluation over 1,500 sentences from the Pañcatantra text shows the effectiveness of the proposed interface on real corpus data.